MOONEY-RIVLIN AND YEOH HYPERELASTIC CONSTITUTIVE MODELLING FROM INDUSTRIAL RUBBER CIPTA DAYA MANDIRIINSANI INDONESIA COMPANY AND JoRGEN BERGSTRoM LITERATURE - PRIHONO (NIM : 13104162); Pembimbing 1 : Dr. Ir. Bagus Budiwantoro; Pembimbing 2 : Dr. Ir. A, GUSTOM
Need an effort to know the properties and characteristics of the rubber, one way is doing a research about mechanics of rubber material. In industrial sector, the properties and characteristics of the rubber can be used to analize failure and predict the life of rubber components under service loading condition. Constitutive modeling is one of the first steps in these efforts. Constitutive modelling that is used to approach hyperelastic characteristics curve of the rubber are Mooney-Rivlin’s deformation energy function in various parameters, and Yeoh’s deformation energy function in various ordes. Then find the error between the model and the experimental/actual data. The acceptable model which have minimum error’s value is selected to represents hyperelastic characteristics curve of rubber. The best model for the first case, uniaxial tension on CDM company’s rubber are Mooney-Rivlin’s model with nine parameters provides the best fit for NR in all strain rate, NR+ with 2 mm/minute strain rate, and NBR in all strain rate. Otherwise for NR+ with 19.8 mm/minute and 198 mm/minute strain rate the best fit is Mooney- Rivlin’s model with five parameters. The best model for the second case, uniaxial tension, biaxial tension, and planar test on Jörgen Bergström’s rubber is three order Yeoh’s model. The value of coefficient on each model can also obtained.